Evidence-based decisions for the wiki world. (11th November 2009) - Pascual, Pasky
US President Barack Obama imagines a 'deliberative democracy' that establishes policies born of the give-and-take of an engaged citizenry, but that also recognises that environmental policies must conform to the scientific evidence. But when online discussions can be easily bombarded by misinformation on complex issues, how should scientific evidence be integrated into environmental policies that are at once politically credible, legally defensible and scientifically sound? This paper describes how recent developments in US administrative law, information technology and statistical analysis create potent new tools to foster environmental policies based on the evidence.